Music and the politics of negation - Currie, James R. (Musical meaning and interpretation, 2012)
Over the past quarter century, music studies in the academy have their postmodern credentials by insisting that our scholarly engagements start and end by placing music firmly within its various historical and social contexts. In Music and the Politics of Negation, James R. Currie sets out to disturb the validity of this now quite orthodox claim. Alternating dialectically between analytic and historical investigations into the late 18th century and the present, he poses a set of uncomfortable questions regarding the limits and complicities of the values that the academy keeps in circulation
Keywords: Musicology; Postmodernism; Music : Political aspects